DEVELOPING A ZERO ORGANIC WASTE TO LANDFILL-BASED ORGANIC WASTE MANAGEMENT MODEL TO SUPPORT SUSTAINABLE TOURISM: A CASE STUDY OF COMO UMA CANGGU, BALI - Sri Widowati; Ida Bagus Udayana Pidada (Antis-Publisher, 2026)
Objective: This study aims to analyze the implementation of the Zero Organic Waste to Landfill program at COMO Uma Canggu through the management functions of Planning, Organizing, Actuating, and Controlling (POAC), and to examine its contribution to sustainable tourism based on the Triple Bottom Line (People, Planet, Profit) and the Environmental Management System (EMS) framework. Method: A qualitative single-case study approach was employed. Data were collected through in-depth interviews with 21 informants, field observations, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. Results: The findings indicate that the hotel has successfully integrated POAC into an EMS-based organic waste management system through source segregation, composting, Black Soldier Fly (BSF) larvae processing, Eco Enzyme production, and continuous monitoring supported by the Green Team. The Waste Diversion Rate increased from 42.5% in 2023 to 63% in 2025, demonstrating a substantial reduction in landfill disposal while generating environmental, social, and economic benefits. Novelty: This study contributes a practical model of organic waste management that can be adopted by hotels and tourism destinations seeking to strengthen sustainable tourism through circular resource management and environmentally responsible operations.